IMPROVING SKILLS FOR WRITING EXPLANATORY TEXTS THROUGH PROBLEM-BASED LEARNING MODEL BY USING CHRONOLOGICAL IMAGE MEDIA OF FOREST FIRE AND HAZE EVENTS - Indra Perdana; Wardani Dwi Wihastyanang; Lazarus Linarto; Joni Bungai (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
This study used a class action research (CAR) method, which was carried out in cycle I and cycle II that consists of the stages of planning, action, observation, and reflection. The data collection in this study used test and non-test techniques and to analyze the data was carried out quantitatively and qualitatively, with a classical completeness target of 85%, with a KKM value of 78, and a KKM value of attitude with a predicate (B). Based on the results, the learning process of compiling explanatory texts has increased in every aspect of his observations, with an average value of three observers of 79.7% not reaching 85% in the first cycle, increasing in the second cycle by 95.14%, or an increase of 10.14%. For the results of an increase in the composition of the explanatory text, compilation increased from the results of pre-cycle, cycle I, and cycle II by 76.3% increased in cycle I by 80% increased in cycle II with an average value of 83.3%, or with a percentage the increase between pre-cycle I to cycle I was 3.7% and between cycle I to cycle II by 15%. The results of students' responses from cycle I to cycle II experienced changes with the results of responses that were getting better or positive in cycle II related to activities learning to compose explanatory texts with Problem Based Learning (PBL) using media images of natural events of forest fires and haze in Central Kalimantan that occur every year during the dry season.